Endoscopic Retrograde Cholangiopancreatography: Therapeutic/Diagnostic Modality and Outcome Analysis - Priya, Khushboo; Pandey, Rajesh; Shrestha, Rishab; Sah, Dipak Kumar; Yadav, Kajol (Journal of Nobel Medical College, 2025)
Background: Endoscopic Retrograde Cholangiopancreatography is an essential therapeutic modality for pancreaticobiliary diseases, but its outcomes and complication rates vary across clinical settings. This study assesses indications, success rates, and complications of Endoscopic Retrograde Cholangiopancreatography (ERCP) in a tertiary care center in Nepal.Materials and Methods: A prospective cross-sectional study was conducted at the Department of Gastroenterology, Nobel medical college teaching hospital, from November 2024 to October 2025. All adults undergoing ERCP for therapeutic indications were included. Demographics, indications, procedural details, and complications were recorded. Statistical analysis was performed using SPSS version 26, with chi-square tests applied to assess associations.Results: A total of 151 patients underwent ERCP, with a mean age of 55 ± 16.5 years; females accounted for 63.6%. Choledocholithiasis was the most common indication (76.8%). Selective biliary cannulation was successful in 97.4%, and overall procedural success was 90.7%. Endoscopic sphincterotomy was performed in 88.1% of patients, while 11.9% required precut. Immediate complications occurred in 19.2%, most commonly post-ERCP pancreatitis (5.3%) and bleeding (5.3%). Papilla type showed a statistically significant association with complications (p = 0.006).Conclusion: Most patients underwent ERCP for benign diseases like common bile duct (CBD) stone and benign biliary stricture. Despite extensive research and refinement of this technique ERCP-related complications remain a major issue. The identification of risk factors for ERCP-related complications and implementation of measures that decreases the risk of complications and its prompt identification and treatment are key to ensuring good clinical outcomes.